THE INFORMATION TECHNOLOGY-BASED PUBLIC-PRIVATE PARTNERSHIP AT THE DEPARTMENT OF LABOUR - Pillay, Kesavel (My University, 2011)
The outcome of the Public-Private Partnership (PPP) implemented at the Department of Labour will be significant to assess the feasibility of future Information Technology based PPPs. The purpose of this research has been to interview the participants involved in the PPP in order to understand the benefits, measurable outcomes, issues, critical success factors and the possible future direction of IT based PPPs. The research findings have shown that there has been noticeable benefits and positive outcomes established thus far. In addition, several issues and critical success factors need to be addressed to improve the perception and future success of the PPP. The complexity and immaturity of PPP contracts make these difficult to evaluate through any quantitative study. The majority of the respondents of this study felt that a PPP was more viable than other forms of IT service offerings and indicated that IT based PPPs will increase in South Africa
MBA thesis - WBS
Keywords: Public-private partnerships; Department of Labour; Information technology